Better Results for Trigonometrically Convex Functions via Hölder-İşcan and Improved Power-Mean Inequalities - Mahir Kadakal (Universal Journal of Mathematics and Applications, 2020)
In this paper, using Hölder-İşcan and improved power-mean integral inequalities and together with an integral identity, we obtain Hadamard type inequalities for functions whose second derivatives in absolute value at certain power are trigonometrically convex functions. In addition, we prove that our results give better approach than previous results.